Exploring Pharmacological Mechanisms of Xuefu Zhuyu Decoction in the Treatment of Traumatic Brain Injury via a Network Pharmacology Approach. (4th October 2018) - Zhong, Yuanyuan; Luo, Jiekun; Tang, Tao; Li, Pengfei; Liu, Tao; Cui, Hanjin; Wang, Yang; Huang, Zebing
Abstract : Objectives . Xuefu Zhuyu decoction (XFZYD), a traditional Chinese medicine (TCM) formula, has been demonstrated to be effective for the treatment of traumatic brain injury (TBI). However, the underlying pharmacological mechanisms remain unclear. This study aims to explore the potential action mechanisms of XFZYD in the treatment of TBI and to elucidate the combination principle of this herbal formula. Methods . A network pharmacology approach including ADME (absorption, distribution, metabolism, and excretion) evaluation, target prediction, known therapeutic targets collection, network construction, and molecule docking was used in this study. Results . A total of 119 bioactive ingredients from XFZYD were predicted to act on 47 TBI associated specific proteins which intervened in several crucial pathological processes including apoptosis, inflammation, antioxidant, and axon genesis. Almost each of the bioactive ingredients targeted more than one protein. The molecular docking simulation showed that 91 pairs of chemical components and candidate targets had strong binding efficiencies. The "Jun", "Chen", and "Zuo-Shi" herbs from XFZYD triggered their specific targets regulation, respectively. Conclusion . Our work successfully illuminates the "multicompounds, multitargets" therapeutic action of XFZYD in the treatment of TBI by network pharmacology with molecule docking method. The present work may provide valuable evidence for further clinical application of XFZYD as therapeutic strategy for TBI treatment.